2018
DOI: 10.1371/journal.pone.0202481
|View full text |Cite
|
Sign up to set email alerts
|

Application of Venn's diagram in the diagnosis of pleural tuberculosis using IFN-γ, IP-10 and adenosine deaminase

Abstract: BackgroundPleural tuberculosis (PlTB) is the most common extrapulmonary manifestation of this infectious disease which still presents high mortality rates worldwide. Conventional diagnostic tests for PlTB register multiple limitations, including the lack of sensitivity of microbiological methods on pleural specimens and the need of invasive procedures such as pleural biopsy performance. In this scenario, the search for biological markers on pleural fluid (PF) has been the target of several studies as a strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…An IFN‐γ concentration above 140 pg/mL has a sensitivity of 94% for TB effusion and a concentration above 240 pg/mL has a sensitivity of 95% . Recently, the combination of high ADA and IFN‐γ was reported to have a specificity and PPV of 100% . The optimal threshold value for identifying tuberculous effusions remains to be identified, and unfortunately the assay remains prohibitively expensive in most environments.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…An IFN‐γ concentration above 140 pg/mL has a sensitivity of 94% for TB effusion and a concentration above 240 pg/mL has a sensitivity of 95% . Recently, the combination of high ADA and IFN‐γ was reported to have a specificity and PPV of 100% . The optimal threshold value for identifying tuberculous effusions remains to be identified, and unfortunately the assay remains prohibitively expensive in most environments.…”
Section: Diagnosismentioning
confidence: 99%
“…56,64 Recently, the combination of high ADA and IFN-γ was reported to have a specificity and PPV of 100%. 65 The optimal threshold value for identifying tuberculous effusions remains to be identified, and unfortunately the assay remains prohibitively expensive in most environments. A commercially available costeffective assay is currently being developed.…”
Section: Tb Effusionmentioning
confidence: 99%
“…In a study about the TB eye disease, the cutoff of QFT was 2 IU/mL, indicating that the cutoff value that was higher than that provided by the manufacturer should be considered to better identify ocular inflammation that is beneficial for full anti-TB treatment [34]. For the diagnosis of TB pleurisy, QFT had the best performance with a cutoff point of 2.33 IU/mL [35]. Another study about the diagnosis of tuberculous pleurisy pointed out that the optimal cutoff of QFT was 0.73 IU/mL for TB Gold assay in blood assay, 0.82 IU/mL for the cultured pleural fluid assay, and 0.94 IU/mL for isolated pleural cell assay [36].…”
Section: Gastroenterology Research and Practicementioning
confidence: 99%
“…Consequently, the development of a rapid and noninvasive bioassay is essential for the diagnosis of tuberculosis infection status. Different studies have proposed that both individual and/or combined cytokines can act as potential biomarkers in differentiating PTB from LTBI [12,15,19,22,23] as well as for the detection of EPTB [13,14,24]. In this study, we employed RT-qPCR to analyze the relative gene expression of cytokines that were stimulated as a part of the bioassay for discriminating tuberculosis infection status, which offers a better advantage with increased sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…QuantiFERON-TB Gold In-Tube (QFT-GIT) test also has a limitation in diagnosing EPTB. Although studies have proposed various diagnostic markers, accurate detection of EPTB remains elusive [13,14]. A previous study has shown that the implementation of combined markers might be useful for distinguishing various infection statuses [15].…”
Section: Introductionmentioning
confidence: 99%